Homemade bread: Repurposing an ancient technology for in vitro tissue engineering. (January 2022) - Holmes, Jessica T.; Jaberansari, Ziba; Collins, William; Latour, Maxime Leblanc; Modulevsky, Daniel J.; Pelling, Andrew E.
Abstract: Numerous biomaterial scaffolds have been developed which provide architectures to support the proliferation of mammalian cells. Scaffolds derived from plant components have been utilized in several tissue engineering applications, including the production of cultured meats. Bread crumb is a common ingredient employed as a texturizer and filler in existing manufacturing processes for the production of animal meat products. Though an unconventional choice as a scaffolding material, we developed a yeast-free "soda bread" with controllable porosity and mechanical properties which is stable over several weeks in culture with fibroblasts, myoblasts and pre-osteoblasts. All cells were able to proliferate throughout the three-dimensional scaffolds, depositing extra-cellular matrix while exhibiting low stress and high viability. Importantly, myoblasts were also able to differentiate into myotubes, a key step required for the culture of skeletal muscle tissue. The results suggest opportunities for the dual-use possibility of utilizing existing texturizer and filler components in future lab grown meat products, however this will of course require further validation. Regardless, the bread-derived scaffolds presented here are simply produced, inherently edible and support muscle tissue engineering, qualities which highlight their utility in the production of future meat products.